Signal analysis of heart sound using spectrogram - Wan Nor Zakaria, Wan Muhammad Aizuddin (2014)
The heart sounds of human in normal good condition typically contain two distinct sound of S1 and S2 that occur in each heartbeat cycle. The respective frequency and time latencies of each tone in heartbeat are important parameters to monitor cardiac function and diagnosis for any abnormality of heart functions. A conventional phonocardiogram analysis using stethoscope can be subjective and imprecise because of heart sound classification analysis depends on the physician interpretation. This paper proposes a spectrogram method which is one of digital signal processing technique to analyze heart sound pattern and to classify for its various diseases related.